2018
DOI: 10.17344/acsi.2017.3728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Pre-treatments on Bioethanol Production from Chlorella minutissima

Abstract: In recent years, algal bioethanol production comes into prominence as a trend towards sustainable development. Due to being sustainable energy source and environmental friendly, bioethanol production from algae is becoming increasingly popular all over the world. However, yield of bioethanol production from algae is lower than first generation feedstock's currently, and needs to be improved. In order to increase bioethanol yield, pre-treatments should be performed as cell disruption process on algal biomass. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 22 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…Moreover, comparatively dilute acids effectively remove hemicellulose as dissolved sugars, and due to the removal of hemicellulose the glucose yield from cellulose also increases resulting in an enhanced yield of sugars [19]. The results suggest that with increase in temperature there is a simultaneous increase in the sugar content which is in agreement with the literature reports [2,3]. For temperature higher than 120 °C, the yield of reducible sugar is found to decrease.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Moreover, comparatively dilute acids effectively remove hemicellulose as dissolved sugars, and due to the removal of hemicellulose the glucose yield from cellulose also increases resulting in an enhanced yield of sugars [19]. The results suggest that with increase in temperature there is a simultaneous increase in the sugar content which is in agreement with the literature reports [2,3]. For temperature higher than 120 °C, the yield of reducible sugar is found to decrease.…”
Section: Resultssupporting
confidence: 88%
“…of 1N and reaction time of 60 min. The results of the study are shown in Fig 5.The results suggest that with increase in temperature there is a simultaneous increase in the sugar content which is in agreement with the literature reports[2,3]. For temperature higher than 120 °C, the yield of reducible sugar is found to decrease.…”
supporting
confidence: 88%
See 3 more Smart Citations